People who cheat on tests accurately predict their performance on future tests. (April 2020) - Undorf, Monika; Mah, Eric Y.; McDonald, Dawn-Leah L.; Hamzagic, Zachariah I.; Burnell, Ryan; Garry, Maryanne; Bernstein, Daniel M.
Abstract: Studies suggest that people who cheat on a test overestimate their performance on future tests. Given that erroneous monitoring of one's own cognitive processes impairs learning and memory, this study investigated whether cheating on a test would harm monitoring accuracy on future tests. Participants had the incentive and opportunity to cheat on one (Experiments 1, 2, and 3, with N = 90, 88, and 102, respectively) or two (Experiment 4, N = 214) of four general-knowledge tests. Cheating produced overconfidence in global-level performance predictions in Experiment 2 (Cohen's d ≥ 0.35) but not in Experiments 1 or 4. Also, cheating did not affect the absolute or relative accuracy of item-level performance predictions in Experiments 3 or 4. A Bayesian meta-analysis of all experiments provided evidence against cheating-induced overconfidence in global- and item-level predictions. Overall, our results demonstrate that people who cheat on tests accurately predict their performance on future tests. Highlights: Examined how test cheating affects performance predictions for future tests. Cheating did not affect the accuracy of global-level predictions. Cheating did not affect the accuracy of item-level predictions. Monitoring accuracy is robust against test cheating.